PENERAPAN SMART VILLAGE DI WILAYAH PINGGIRAN DESA GROGOL KECAMATAN SAWOO KABUPATEN PONOROGO - Juliantoro, Mohammad Andik; Nasution, Robby Darwis; Harsono, Jusuf; Triono, Bambang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research, entitled Application of Smart Villages in the Outskirts, aims to find out how the concept of the Digital Village program can be applied in suburban areas far from urban areas. In the current era of modern, technological developments are very rapid, especially the development of the internet which gives rise to new cultures in society. The internet is no longer foreign to the public, almost all people feel the changes with the development of the internet. The method used in this research is In this study the approach taken is through a qualitative approach. The research was conducted in one of the suburbs in Ponorogo Regency, namely Grogol Village, Sawoo District. Digital village is a program concept that implements government service systems, community services, and community empowerment based on the use of information technology. Grogol Village is the only village which was inaugurated by the Regent of Ponorogo as a digital village. The